Edukasi tentang Makna Panggilan dan Iman Bagi Peserta Didik SMK Negeri 7 Batam - Refamati Gulo; Ramayani Nggadas; Jeppri Nainggolan; Deskin Kevin Demitri Walanda; Suliana; Martinus Lahagu; Angelia Manoppo (Vieka Wahana Semesta, 2026)
Abstract This Community Service Program aims to provide structured education on the meaning of calling and faith to students of SMK Negeri 7 Batam. Vocational education students generally focus more on mastering technical skills without engaging in reflective exploration of life meaning, moral values, and spiritual identity. Drawing upon studies in vocational psychology, character education, and adolescent development, this program integrates interactive seminars, guided reflection, and participatory discussions to help students understand career as a life calling rather than merely employment. The methods employed include reflective workshops, values clarification, and contextual approaches tailored to students’ developmental stages. The expected outcomes include increased clarity of life purpose, enhanced moral awareness, strengthened intrinsic motivation, and alignment between vocational competence and ethical responsibility. This program contributes to holistic education by integrating spiritual meaning with work readiness. Abstrak Kegiatan Pengabdian kepada Masyarakat ini bertujuan memberikan edukasi terstruktur mengenai makna panggilan dan iman kepada peserta didik SMK Negeri 7 Batam. Peserta didik pendidikan vokasi umumnya lebih terfokus pada penguasaan keterampilan teknis tanpa pendalaman reflektif mengenai makna hidup, nilai moral, dan identitas spiritual. Berdasarkan kajian psikologi vokasional, pendidikan karakter, dan perkembangan remaja, program ini mengintegrasikan seminar interaktif, refleksi terpimpin, serta diskusi partisipatif untuk membantu peserta didik memahami karier sebagai panggilan hidup, bukan sekadar pekerjaan. Metode yang digunakan meliputi lokakarya reflektif, klarifikasi nilai, dan pendekatan kontekstual sesuai tahap perkembangan peserta didik. Luaran yang diharapkan adalah meningkatnya kejelasan tujuan hidup, kesadaran moral, motivasi intrinsik, serta keselarasan antara kompetensi vokasional dan tanggung jawab etis. Program ini berkontribusi pada pendidikan holistik dengan mengintegrasikan makna spiritual dan kesiapan kerja.